Maori and Pasifika higher education horizons - Cram, Fiona (Bingley, U.K. : Emerald, 2014)
Rarely have Pasifika writers come together to share their experiences in this field. Focusing on the past, current and future status and success of Maori and Pasifika peoples in tertiary education within Aotearoa New Zealand, this volume covers diverse issues from the countries colonial history, to student engagement with new technology.
Whaia / Te Maramatanga : seek knowledge / Pale Sauni ... [et al.] -- Indigenising the academy : a case for intercultural institutional mediating structures for Aotearoa/New Zealand / Wally Penetito -- WAnanga : a distributive action / Rosina Taniwha -- Ranga : an indigenous cognitive development framework / Wiremu Doherty -- Te Timata : the first step to Maori succeeding in higher education / Margaret Wilkie -- Te Tapuae o Rehua : IWI engagement in higher education in Te Waipounamu / Catherine Savage ... [et al.] -- Realising indigenous imperatives through institutional transformation / Janine Kapa-Blair, Mark Brunton -- Intangible knowledge systems : their application in tertiary institutions and the impact they have on Iwi Maori staff / Khyla Russell -- My sixth sense tells me / Pale Sauni -- Decolonising the academy : the process of re-presenting indigenous health in tertiary teaching and learning / Elana Curtis, Papaarangi Reid, Rhys Jones -- Dreaming ourselves into places of higher learning : indigenous psychologies at the university of Waikato / Linda Waimarie Nikora -- Awhina reloaded : updated results from a programme for Maori and Pacific tertiary graduate and postgraduate success in science, engineering, and architecture and design / Ken Richardson ... [et al.] -- Optimizing Maori academic achievement (OMAA) : an indigenous led, international, inter-institutional higher education initiative / Lorrí Santamaría, Jenny Bol Jun Lee, Ngaira Harker -- The development of mentoring relationships for Pacific Students in a New Zealand university : possibilities for leadership / Cherie Chu -- From schools in low-income communities to university : challenges of transition for Maori and Pacific students / Elizabeth McKinley, Irena Madjar -- Journeys into higher education for Maori students with impairments : charting the terrain of inclusive higher education in Aotearoa / Hazel Phillips, Kahurangi Tibble -- Samoan women in tertiary education and ethnic identity / Diane Mara -- Hinerauwhariki : the collective higher education experiences of four Maori women / Ngahorihori Wehipeihana ... [et al.] -- He mihi mutunga : closing words / Fiona Cram ... [et al.].
Includes index.
Print version record
Keywords: Education -- Multicultural Education; Education -- Higher; Higher & further education, tertiary education; Education; Maori (New Zealand people) -- Education (Higher) -- New Zealand; Pacific Islanders -- Education (Higher) -- New Zealand; Universities and colleges -- New Zealand -- Sociological aspects; Education, Higher -- New Zealand